Evaluation of Antifungal Activity of ZnO Nanoparticle Against Saccharomyces Cerevisiae (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Zinc oxide nanoparticles (ZnO NPs) are among the most frequently utilized nanomaterials because they inhibit microbial growth; however, their precise mode of action (MOA) remains incompletely understood. This study details the synthesis of zinc oxide (ZnO) nanoparticles via the sol-gel method, selected for its high purity, homogeneity, and precise controllability. The research evaluates the impact of calcination temperature on the structural, morphological, and antimicrobial properties of the resulting particles. Characterization was conducted using X-ray diffraction (XRD), thermogravimetric analysis (TGA), and Fourier-transform infrared spectroscopy (FTIR) to determine crystallite size and surface composition. Additionally, the antifungal efficacy of the synthesized ZnO nanoparticles was rigorously tested against Saccharomyces cerevisiae to assess their potential as bioactive agents. The nanoparticles' ability to fight fungus was then assessed using the yeast strain Saccharomyces cerevisiae. The findings indicated that the ZnO nanoparticles did not demonstrate any antifungal effect against Saccharomyces cerevisiae. The minimal toxicity observed in both nano and bulk forms of ZnO towards this yeast is likely attributable to S. cerevisiae's notable tolerance for high concentrations of zinc ions.